A PENGARUH MOTIVASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA PEGAWAI SMP NEGERI 3 DI BERAU: PENGARUH MOTIVASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA PEGAWAI SMP NEGERI 3 DI BERAU - Endah Susanti (ECO-BUILD, 2018)
This study aims to explain whether the variables of Motivation and Leadership Principal influence significantly to the Performance of Junior High School 3 Officials in Berau. The result of hypothesis testing (H1) has proved there is no influence between motivation on employee performance. Through the calculation results have been done t value arithmetic -1.250 with a significance level of results of 0.227> É‘ (0.05), thus the first hypothesis is not proven Hypothesis testing result (H2): there is no influence of headmaster leadership on employee performance. Through the calculation results have been obtained t value arithmetic -0.567 with a significance level of results of 0.577> É‘ (0.05), thus the second hypothesis is not proven Hypothesis testing result (H3) has proved there is no influence between motivation and leadership of headmaster to employee performance. Through the calculation results have been obtained obtained f value 0.742 with the significance of results of 0.490> É‘ (0.05), thus the third hypothesis is not proven.